Pengaruh Ekspor, Nilai Output, dan Kredit Korporasi ppada Sektor Padat Karya Terhadap Tingkat Pengangguran Terbuka di Pulau Jawa Tahun 2011-2023 - Ega Amri Sabili (Indo Publishing, 2026)
This study aims to measure the impact of Exports, Output Value, and Corporate Credit on the Open Unemployment Rate within the labor-intensive manufacturing sector across six provinces in Java (2011–2023). This sector faces challenges of deindustrialization and a shift toward capital-intensive industries, triggering structural unemployment. Utilizing panel data from Statistics Indonesia and Bank Indonesia, analyzed through Path Analysis with a Random Effect Model (REM), this research examines both direct and indirect relationships among these variables. The findings reveal that the three independent variables simultaneously account for 24.9% of the unemployment fluctuation. Partially, Output Value emerges as the most dominant and effective factor in directly reducing unemployment, as the traditional manufacturing sector remains highly reliant on human labor. Conversely, Exports and Corporate Credit are proven to directly increase unemployment; this occurs because export activities and credit allocations are increasingly directed toward automation and technological modernization. Nevertheless, the indirect interaction analysis proves that the synergies between Exports and Output Value, as well as Corporate Credit and Exports, successfully mitigate unemployment by expanding domestic production capacity. In conclusion, enhancing Output Value remains the strongest instrument for labor absorption, while exports and credit allocation require policy alignment to prevent industrial expansion from focusing exclusively on capital-intensive technology.